Stability analysis of SDOF real time hybrid testing systems with explicit integration algorithms and actuator delay. - Chen, Cheng
Real time hybrid testing is a method that combines experimental substructure(s) representing component(s) of a structure with a numerical model of the remaining part of the structure. These substructures are combined with the integration algorithm for the test and the servo-hydraulic actuator to form the real time hybrid testing system. The inherent dynamics of the servo-hydraulic actuator used in real time hybrid testing will give rise to a time delay, which may result in a degradation of accuracy of the test, and possibly render the system to become unstable. To acquire a better understanding of the stability of a real time hybrid test with actuator delay, a stability analysis procedure for single degree of freedom structures is presented that includes both the actuator delay and an explicit integration algorithm. The actuator delay is modeled by a discrete transfer function and combined with a discrete transfer function representing the integration algorithm to form a closed loop transfer function for the real time hybrid testing system. The stability of the system is investigated by examining the poles of the closed loop transfer function. The effect of actuator delay on the stability of a real time hybrid test is shown to be dependent on the structural parameters as well as the form of in the integration algorithm. The stability analysis results can have a significant difference compared with the solution from the delay differential equation, thereby illustrating the need to include the integration algorithm in the stability analysis of a real time hybrid testing system.
Keywords: Hybrid testing; Real time; Integration algorithm; Stability; Actuator delay; Discrete transfer function; Closed loop